Spatial Determinants of Productivity: Analysis for the Regions of Great Britain. - Rice, P; Venables, A (Centre for Economic Performance, LSE, 2004)
This paper uses NUTS3 sub-regional data for Great Britain to analyse the determinants of spatialvariations in income and productivity. We decompose the spatial variation of earnings into aproductivity effect and an occupational composition effect. For the former (but not the latter) wefind a robust relationship with proximity to economic mass, suggesting that doubling thepopulation of working age proximate to an area is associated with a 3.5% increase in productivityin the area. We measure proximity by travel time, and show that effects decline steeply with time,ceasing to be important beyond approximately 80 minutes.